FAMILY SMOKING STATUS AND PHYSICAL HOUSE CONDITION WITH THE PULMONARY TUBERCULOSIS IN PRE-PROSPEROUS ECONOMIC COMMUNITY - Shalsabiila Alkatiri; Yunus Arianto; Arina Mufida Ersanti (Universitas Airlangga, 2023)
Background: According to the 2019 Indonesian Health Profile, there were 663 tuberculosis cases per 100,000 people, with 1,001 cases in Nganjuk Regency during the pre-prosperous period. Poverty had an impact on densely populated housing as well as bad smoking habits. The purpose of this study is to determine the relationships between family smoking status and tuberculosis in the home in the pre-prosperous group. Methods: Case group quantitative research was random, including the incidence of TB from January 2019-December 2020 in the working area of Prambon Public Health Center, Nganjuk Regency; the control group took the closest contact neighbor of the case sample. The category of pre-prosperous was based on the 2011 Central Statistics Agency's Social Protection Program. The study was conducted from October 2020-April 2021. Data collection was done through interviews, observation, and measuring the physical house (rollmeter, luxmeter, and a thermohygrometer). Data analysis used chi-square and multivariate tests. Results: The bivariate analysis found the correlations on males (p: 0.02; OR: 3.17), productive age (p: 0.01; OR: 0.22), smoker (p: 0.22; OR: 2.42), humidity <40% and >60% (p: 0.04; OR: 3.14), lighting <60 lux (p: 0.00; OR: 4.84), ventilation <40% of floor area (p: 0.04; OR: 3.40), damp floor (p: 0.01; OR: 3.50) and damp wall (p: 0.04; OR: 2.81) with TB. Active smoking was the most influential variable (OR 44.00). Conclusion: It is hoped that local health agencies will be able to provide more education about smoking habits through the simple implementation of a healthy house area empowerment program.